Prevalence of Noise Induced Hearing Loss among Employees at Wood Industry in Damietta Governorate - Waheed Elsaidy (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: Occupational noise-induced hearing loss (ONIHL) is a major health issue with high prevalence globally and has major social, economic and psychological effects. Aim of the work: Assessment of noise induced hearing loss (NIHL) prevalence among employees at wood industry in Damietta governorate. Patients and methods: The present cross-sectional study was carried out in New Damietta city, Damietta governorate, Egypt. Ten workplaces were selected through convenience sampling. From these ten workplaces, one hundred fifty (150) employees agreed to participate in the study. Pure-tone audiometry between 500 and 8000Hz frequencies determined the hearing condition of the participants and noise readings were conducted at the selected workplaces. Results: Among all study participants, the prevalence of noise induced hearing loss (NIHL) was 39% of carpenters and 44.4% of sawyers with no statistically significant difference (P = 0.253) between both groups. Noise levels ranged from 73 to 91.5 dBA in the various furniture factories and from 74.9 to 94.1 dBA in the different saw mills. Conclusion: Occupational noise induced hearing loss (ONIHL) is highly prevalent in Damietta governorate among wood workers, which might be due to lack of knowledge, awareness about NIHL among employers, workers, and health care workers along with absence and or implementation of hearing conservation programs in the work places.